COMMUNITY STRUCTURES OF EPIPELIC DIATOM AS A BIOINDICATOR IN CAWAN ISLAND OF INDRAGIRI RIVER’S ESTUARY OF INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Shofian Nanda Adiprayoga; Sofyan Husein Siregar; Joko Samiaji (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study on diatom epipelic has been conducted in Cawan Island coastal waters of Indragiri River’s estuary, Riau Province. The main purpose of this research was to learn the community structures of epipelic diatom and water quality conditions. The method used were consisting of field survey and data gathering from related parties. The epipelic diatom samples were collected by using 5x5 cm2  plots. Diatom samples and water quality analysis were done in Marine Biology Laboratory of Faculty of Fishery and Marine Science. The results showed that community structures of epipelic diatom had intermediate level of contaminant. The 2 indexes, i.e.the diversity index (H’) and the eveness index (E’), were calculated at the values of  2.768 and  0.499, respectively. As for the dominant index (D) the value was at 0.176. Most of the parameters value of water quality (chemical and physics) were in the range of the aquatic organisms life. Statistical analysis showed the abundance of epipelic diatom between station were relatively similar. Keywords: Diatom Epipelic, Estuary, Coast, Cawan Island